Internet- and mobile-based approaches: Psycho-social diagnostics and treatment in medical rehabilitation - Baumeister, Harald; Lin, Jiaxi; Ebert, David (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2017)
Technology-based approaches for psychosocial diagnostics and interventions provide an attractive opportunity to optimize medical rehabilitation. Based on an Internet- and mobile-based assessment of existing functional health impairments, appropriate planning, implementation of corresponding courses of action as well as outcome assessment can take place. This can be implemented in the form of Internet- and mobile-based interventions (IMI). The present article provides an overview of the basic knowledge of IMI and their evidence base both in general and in particular for their use in medical rehabilitation. Important aspects of internet and mobile-based psycho-social diagnostics are discussed subsequently. Finally, an outlook for the use of Internet- and mobile-based diagnostics and interventions in medical rehabilitation is give
Keywords: E-Health; Internet- and mobile-based interventions; Medical rehabilitation; Psychological interventions; Technology-based diagnostics